50 MeV lithium ion irradiation studies on silicon-germanium heterojunction bipolar transistors at low temperature. (October 2022) - Hegde, Vinayakprasanna N.; Praveen, K.C.; Pradeep, T.M.; Cressler, John D.; Prakash, A.P. Gnana
Abstract: Total dose effects of 50 MeV lithium ions irradiation on 200GHz silicon-germanium heterojunction bipolar transistors (SiGe HBT) in the dose ranging from 1 to 30 Mrad were examined at low temperature. The HBTs were subjected to 50 MeV lithium ions at 150 K and 300 K. Pre- and post-irradiation I-V characteristics were studied at 300 K. The comparison of low temperature irradiation results with room temperature results was made systematically. The radiation caused generation-recombination trapped carriers increase the base current (IB ) of HBTs and is proportional to the total dose. However, the transistors irradiated at 150 K show lesser degradation than devices irradiated at 300 K. Stopping and range of ions in matter (SRIM) study was also carried out to know the impact of lithium ions on different regions of SiGe HBT. Highlights: Reliability of SiGe HBTs was studied under Li ion irradiation at Low temperature. SRIM/TRIM simulation was carried out to understand energy loss mechanism. 50 MeV Li ion induced degradation is less at low temperature than at room temperature. Radiation induced charge yield is less at low temperatures.